Inflammation as the Potential Basis in Depression - Maeng, Sung Ho; Hong, Heeok (International neurourology journal, 2019)
There is growing evidence of the association between inflammation and stress-related disorders including depression. The positive correlation between the increased levels of inflammatory cytokines observed in patients with other diseases and the byproduct of the depressive symptoms may be caused by chronic stress. Increased neuroinflammatory responses are capable of activating microglia and astrocytes, which leads to release pro-inflammatory cytokines. Moreover, elevated levels of inflammatory cytokines such as tumor necrosis factor-alpha, interleukin (IL)-1, and IL-6 are causally related to various aspects of depression such as the behavioral symptomatology. Eventually, these elevated cytokines aggravate and propagate neuroinflammation, impairing brain functions. Thus, activated astrocytes and microglia may be potential mediators in neuroinflammatory processes contributing to the development of depression.